Pengembangan Media Pembelajaran Teka Teki Silang Materi Alat Gerak dan Fungsinya pada Hewan untuk Siswa Kelas V Sekolah Dasar - Fajar Riyani; Wahid Ibnu Zaman; Ita Kurnia (DIMAR: Jurnal Pendidikan Islam, 2023)
Learning media is one of the visual aids that students really need in learning activities. This can be proven from the function of the learning media itself, which can facilitate the delivery of material in learning. So that students can easily understand or accept the material presented. Learning media must also be designed or developed creatively and innovatively so that students are more interested. One method that can be developed in designing instructional media for elementary school students is using packaged media using games. Students will be interested in something that is conveyed by using games, but also does not fade the learning values. One game that can support students in learning is a crossword puzzle. Namely a game where the players have to fill in the empty spaces both vertically and horizontally with the letters that form a word based on the instructions given. For example, in class V of elementary school, the subject that is suitable for the development of this learning media is science with the arteries of the locomotor and its function in animals.